Effect of feeding crop residues of different cereals and legumes on weight gain of Yankassa rams - Singh, B.B.; Musa, A.; Ajeigbe, Hakeem A.; Tarawali, Shirley A. (2011)
Crop residues from maize (Zea mays L.), sorghum (Sorghum bicolor L. Moench), millet (Pennisetum glaucum), cowpea (Vigna unguiculata L. Walp) and groundnut (Arachis hypogaea L.) are important livestock feed in the West African savannas particularly during the long dry season. The residues from cereal crops are relatively in abundance, but of low nutritive value compared to the leguminous crop residues, which are normally in short supply. This experiment was conducted to determine the most efficient combinations of feeding crop residues of major cereals and legumes with and without bran supplement to ‘Yankassa’ rams in confinement over a 70-day period and their effect on weight gains. Feeding the residues of cereals alone resulted in a mean weight loss of 14% for sorghum, 16% for maize and 11% for millet, while feeding the residues of cowpea or groundnut alone resulted in the weight gain of about 13 and 12%, respectively. Supplementing the cereals residues with about 300 g of legume residues per ram per day resulted in slight gain in weight. Addition of 300 g wheat bran and 300 g legume residues to the cereals in the daily diets of each ram resulted in about 19% mean weight gain. Thus, bran showed a small but significant additive effect on weight gain. From the 1.5 kg cereals or legumes residues offered per ram per day, the rams ate about 50% of cereals and 82% of the legumes. Thus, the cereals residues are not only less nutritious, but also less consumable compared to the legumes.